Effect of ionic liquid on the thermal decomposition of cyclic organic peroxides - Barreto, Gastón Pablo (2016)
The thermolysis of cyclic diethylketone triperoxide (3,3,6,6,9,9-hexaethyl-1,2,4,5,7,8-hexaoxacyclononane, DEKTP) and cyclic pinacolone diperoxide (3,6-diterbutyl-3,6-dimethyl-1,2,4,5-tetraoxacyclohexane, PDP) was studied in neat N,N-dimethylformamide (DMF) and in binary mixtures DMF/Ionic Liquid (1-butyl-3-methylimidazolium tetrafluoroborate, [BMIM+][BF4 -]). The activation parameters for the decomposition of both peroxides in DMF, correspond to a process of homolytic cleavage of one OO bond, generating a biradical in the initial step of radical mechanism. The rate constant values (kd ) are higher for reactions performed in mixtures. A gradual increase of [BMIM+][BF4 -] in the reaction media generates higher kd for both peroxides (i.e. kd , DEKTP in DMF/[BMIM+][BF4 -] 4.0molL-1 is 3.3 times greater than the kd obtained for the mixture with a concentration 1.0molL-1, under the same experimental conditions). The increase in decomposition rate can be associated with a more solvated and stabilized transition state when the ionic liquid is part of the reaction medium.